Removal of methylene blue from aqueous solution using cocoa (Theobroma cacao) nib-based activated carbon treated with hydrochloric acid - Nikman, KA; Ahmad, F; Hassan, MS (Penerbit UTM Press, 2024)
Indexed by WOS